Prevalence and antimicrobial resistance profile of Escherichia coli O157:H7 isolated from chickens and chicken meats from local poultry slaughterhouses in Nakhon Ratchasima Province, Thailand - Pattarakitti Noenchat; Thanawan Srithong; Sujeeporn Lertpiriyasakulkit; Chawakorn Nhoonoi; Chuleeporn Saksangawong; Pairat Sornplang (Veterinary Integrative Sciences, 2023)
This study sought to investigate the antimicrobial resistance profiles of Escherichia coli O157:H7 (EOH) isolated from chickens and chicken products at local poultry slaughterhouses in Nakhon Ratchasima Province, Thailand. EOH was isolated from cloacal swabs and chicken breast meat samples between January 2021 and June 2023. EOH were identified using a culture-based method and were confirmed on sorbitol MacConkey agar. Positive EOH isolates were tested via antimicrobial susceptibility testing and antimicrobial resistance profiles using the disk diffusion method and polymerase chain reaction. This study showed the prevalence of EOH isolated from chicken breast meat (11.47%) was higher than that of cloacal swab (9.32%). Most EOH isolates from cloacal swabs were resistant to oxytetracycline (65.38%), streptomycin (61.54%), amoxicillin (61.54%), and ampicillin (65.38%, and most EOH isolates from breast meat were resistant to oxytetracycline (78.12%), streptomycin (25%), amoxicillin (75%), and ampicillin (78.12%). In addition, 32 (55.17%) EOH isolates were multidrug resistant harbored the ESBL-TEM gene (65.38%), blaTEM (34.61%), int-1 (3.85%), or mcr-1 (0%). This is the first report of EOH isolated from chickens and chicken meats from domestic poultry slaughterhouses in Nakhon Ratchasima Province. Therefore, EOH is a public health concern in local poultry slaughterhouse processes in this area.